Televisual Tales From Across the Border: Mapping Neo-Global Flows in Media Peripheries. (December 2019) - Pant, Ritika
Foreign programming on Indian television was largely dominated by American and British TV programmes until 2014, when a Hindi entertainment channel Zindagi, owned by Zee Entertainment Enterprises, began broadcasting syndicated television content from Pakistan. The channel's tagline Jodey Dilon Ko (uniting hearts) shaped the possibility for peaceful reconciliation between the two political rivals, India and Pakistan, by offering ' sarhad paar ki kahaaniyaan ' (stories from across the border) to Indian audiences. The popularity of Pakistani serials in India may be observed against the backdrop of a television industry inundated with formulaic saas–bahu (mother-in-law/daughter-in-law) plotlines over the last decade. While Indian television and films have been a part of Pakistani popular culture for years, Pakistani serials like Humsafar (life partner, 2011) and Zindgai Gulzar Hai (life is a bed of roses, 2012) broadcast on Zindagi gave Indian audiences a peek into their neighbours' socio-cultural environment. These serials dismantled the conventional mediatised image of the distanced 'other' and redefined the former perception of 'foreign' as essentially 'Western' in Indian television programming. Through an analysis of new trajectories of flows between media peripheries that I term 'neo-global' flows, this article argues that Pakistani dramas broadcast on Zindagi between 2014 and 2016 offered a 'mediating space' to Indian audiences by maintaining a balance between Indian tradition and Pakistani modernity.